Brain metastasis incidence in gastro-esophageal cancer: A meta-analysis. (1st June 2022) - Sleiman, M-J; Abbassi, Z; Jung, M; Toso, C; Chevallay, M; Mönig, S
Abstract: Objective: Upper gastrointestinal cancers (UGC) are a leading cause of cancer related deaths. Brain metastases (BM) from gastric and esophageal cancer are rare and associated with a poor survival time. The precise incidence of BM for UGC is lacking. Methods: We searched: "Gastric cancer OR Oesophageal Cancer AND Cerebral Metastasis" in Pubmed, EMBASE, Cochrane Library. Inclusion criteria were all studies with an incidence rate of BM from UGC cancer patients cohort. When the inclusion criteria were met, we extracted the following endpoints: year of publication, country of population, tumor localization, histology, number of brain lesion, synchronous or metachronous brain metastases, stage of the primary tumor, other localization of metastases, surgical treatment of the primary tumor, brain metastasis treatment (surgery, steatosic radiosurgery, whole brain radiation, gamma knife surgery), survival and follow-up. Results: 52 studies were included. The total number of patients with oesophageal tumor were described in 30 studies with 41636 patients from which 1234 patients (2.9%) had BM. 526 patients (63%) had an adenocarcinoma, 287 (34%) had a SCC and 17 (3%) other histology. BM was unique in 288 patients (50%) and multiples in 282 patients (50%). A combined radiotherapy and surgery was performed in 129 patients (17.9%). Surgical metastasectomy was performed in 172 patients (24.25%). Stereotaxic radiotherapy was delivered in 60 patients. (8.5%) A whole brain radiotherapy was performed in 265 patients (35.9%). Gamma knife surgery was performed in 43 patients (5.9%). Chemotherapy in 10 patients (1.6%) and no treatment in 43 patients. (5.9%). The median survival was reported from 3 month to 24 months. We identified 12 articles which matched the research criteria for gastric cancer with a total of 73.781 primary gastric tumors where 645 presented brain metastasis (0.87%). 159 patients had single BM (42.3%) compared to 217 patients with multiple BM (57.7%). We identified 434 adenocarcinoma which represent 81.1% of the brain metastasis. Median survival for patients with brain metastasis from gastric cancer was described from 1.3 month to 27 months. Conclusion: Brain metastases from UGI cancer are rare and associated with a low survival. Multimodal treatment is the most described treatment strategy. More studies are required to assess the role of brain imaging in the initial staging of UGI cancer.